2021
DOI: 10.18240/ijo.2021.10.21
|View full text |Cite
|
Sign up to set email alerts
|

Intraorbital wooden foreign bodies: case series and literature review

Abstract: Intraorbital wooden foreign bodies (IOWFBs) constitute a relatively rare ocular trauma, which occupy a special type of intraorbital foreign bodies (IOFBs). Data regarding IOWFBs must be obtained from case reports or small case series due to their rarity. Here, we reported 5 cases of IOWFBs and reviewed the related literatures, which could provide comprehensive information regarding the clinical manifestations, diagnosis, and surgical treatment of IOWFBs. Combined with the published literature, a total of 51 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
7
0
2
Order By: Relevance
“…Wood's porous organic nature makes it an ideal breeding ground for bacteria and other germs that could cause infection if left untreated ( 5 , 28 , 29 ). It has been reported that more than half of patients with IOWFBs develop an orbital infection ( 9 , 30 , 31 ), necessitating the removal of all wooden foreign bodies. Large foreign bodies should also be removed surgically because they always cause eye movement disorders, oppressive symptoms, and visual dysfunction ( 3 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wood's porous organic nature makes it an ideal breeding ground for bacteria and other germs that could cause infection if left untreated ( 5 , 28 , 29 ). It has been reported that more than half of patients with IOWFBs develop an orbital infection ( 9 , 30 , 31 ), necessitating the removal of all wooden foreign bodies. Large foreign bodies should also be removed surgically because they always cause eye movement disorders, oppressive symptoms, and visual dysfunction ( 3 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 Currently, CT scan remains the gold standard but it has inconsistent reported detection rates ranging from 42% to 72%. 1,2,[5][6][7] The type of wood, density, and freshness leads to variable signal densities on CT. 8 Wooden foreign bodies in the orbit are challenging to diagnose and easily missed on imaging. A clear history with the presumed clinical diagnosis should be provided to radiology for careful assessment of images.…”
Section: Discussionmentioning
confidence: 99%
“…The infection may manifest as orbital cellulitis, abscess formation, and even intracranial infection. Detection of wood in the eye is challenging because it is carbon-containing and not visible on conventional x-ray may not image well on CT or MRI [ 169 , 170 ]. If the chip is small and on the surface, it may be flushed with eyewash; however, deeper penetration shards may require surgical intervention and antibiotic treatment ( Figure 1 ) [ 171 ].…”
Section: Workplace Ocular Injuriesmentioning
confidence: 99%